Transcriptomic responses to hypoxia in two populations of eastern oyster with differing tolerance - Crable, Emma L.; Rodriguez, Heather; Vaidya, Rujuta V.; Coxe, Nicholas; La Peyre, Jerome F.; Kelly, Morgan W. (Frontiers in Marine Science, 2024)
The eastern oyster, Crassostrea virginica, is a keystone species native to the Gulf of Mexico and Atlantic coasts of the United States and Canada. It provides habitat for other marine organisms and makes up the majority of oyster production in the United States. Despite its tolerance to hypoxic conditions, C. virginica is threatened by anthropogenic climate change, which is increasing both average temperature and the frequency and severity of hypoxic events. In this study, we explore the differences in hypoxia-transcriptional response between two populations of eastern oysters with known differences in hypoxia tolerance at three time points over the course of a 5-day hypoxia treatment. We identified sets of genes involved in the hypoxia response and found differences in both the timing and baseline expression of hypoxia-responsive genes between tolerant and sensitive populations, consistent with a scenario of local adaptation. Analysis of differential gene expression between the two populations and conditions revealed two gene modules with higher baseline expression of hypoxia-sensitive genes in the more hypoxia tolerant population. Key GO terms for genes corresponding to differences between populations include DNA repair, ribosome biogenesis, and ribonucleotide binding. Our results imply that differences in hypoxia tolerance between populations could be due to genetic frontloading of hypoxia response pathways in the more tolerant population.